The Effectiveness of a Proposed Blended-Learning Model in Developing Literary Translation Skills of Saudi-University Students - نصر، محمود عبدالناصر (جامعة اليرموك - عمادة البحث العلمي, 2022)
تمثل هدف الدراسة الحالية في تصميم نموذج تعلم تمازجي، واختبار فعاليته في تنمية مهارات الترجمة الأدبية لدى الطلاب الجامعيين السعوديين. شارك في الدراسة 140 طالبا وطالبة. تم توزيع المشاركين بطريقة عشوائية على المجموعتين التجريبية والضابطة. وأوضح التحليل الإحصائي وجود فروق ذات دالة إحصائية بين متوسطي درجات طلاب المجموعتين في التطبيق البعدي للاختبار لصالح المجموعة التجريبية. بينما لم توجد فروق ذات دلالة إحصائية بين متوسطي الذكور والإناث في المجموعة التجريبية في التطبيق البعدي للاختبار. وقد أثبت النموذج فعاليته في تنمية مهارات الترجمة الأدبية لدى الطلاب الجامعيين السعوديين. The purpose of this study was to design a blended learning model and to test its effectiveness in developing literary translation skills of Saudi university students. Participants in the study comprised 140 students (including males and females) distributed randomly between the experimental and control groups. Statistical analysis of the data indicated that there were statistically significant differences between the mean scores of the two groups in the post-administration of the test in favor of those of the experimental group. No significant differences were found between the mean scores of males and females in the experimental group in the post-administration of the test. The suggested model proved to be effective in developing literary translation skills of Saudi university students.
Keywords: التعلم المدمج -- طرق التدريس -- التنمية التعليمية -- مهارات الترجمة -- طلبة الجامعات -- السعودية